Proceedings of the 20th International Conference on Software Engineering
DOI: 10.1109/icse.1998.671389
|View full text |Cite
|
Sign up to set email alerts
|

The ramp-up problem in software projects: a case study of how software immigrants naturalize

Abstract: Joining a software development team is like moving to a new country to start employment; the immigrant has a lot to learn about the job, the local customs, and sometimes a new language.In an exploratory case study, we interviewed four software immigrants, in order to characterize their naturalization process. Seven patterns in four major categories were found. In this paper, these patterns are substantiated, and their implications discussed. The lessons learned from this study can be applied equally to improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 6 publications
1
61
0
Order By: Relevance
“…This has been well reported [4,6,16]. A case study by Sim & Holt of immigrants in a traditional software project noted knowledge barriers to entry and the importance of mentors [19]. This study also noted the need for a "minimal interest match" between a new immigrant and the project.…”
Section: Related Workmentioning
confidence: 94%
See 1 more Smart Citation
“…This has been well reported [4,6,16]. A case study by Sim & Holt of immigrants in a traditional software project noted knowledge barriers to entry and the importance of mentors [19]. This study also noted the need for a "minimal interest match" between a new immigrant and the project.…”
Section: Related Workmentioning
confidence: 94%
“…Knowledge and Skill Level can be expected to increase with the time a person spends with the project. This difficult, time-consuming process of learning the details of a specific system and development environment (sometimes known as discovery, or ramp-up) is documented by prior research [6,19]. In many cases, even the initial email is sent by an individual on the developer mailing list only after some initial study; quite often people submit patches during their first month of activity on the mailing list.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Interestingly, while this issue of socialization has been explored in the context of traditional software engineering groups (e.g. Sim and Holt, 1998), there is much less data and analyses available from the Open Source world.…”
Section: Socialization In An Open Source Software Communitymentioning
confidence: 99%
“…Sim and Holt, for instance, interviewed newcomers to a project and found that they had to learn intricacies about the system, development processes being used, and the organizational structure surrounding the project, amongst others [15]. In collocated teams, this knowledge is often gained through mentoring: An existing member of the team works closely with the newcomer, looking over their shoulder, and imparting the oral tradition of the project, as the newcomer works on their first assigned tasks [15,6].…”
Section: Introductionmentioning
confidence: 99%